Study of Activation Energy ofMagnetohydrodynamic Radiative Casson Nanofluid With Heat Source/sink and Cattaneo Christov Heat Flux Model Over Exponential Stretching Sheet - Younus, Mohammed; Venkatalakshmi, A. (Communications in Mathematics and Applications, 2024)
The present work uses numerical analysis to examine the activation energy (A.E.) of a magnetohydrodynamic (MHD), mixed convective, radiative Casson nanofluid with heat source/sink, Cattaneo Christov’s heat flow model, “zero normal flux of the nanoparticles” across an exponentially stretched sheet, together with convective boundary condition. Numerous parameters’ impacts on the temperature profile, velocity, and concentration profile were graphically interpreted after investigation. The findings are very comparable to those found in openly available literature. The velocity profile was observed for Casson fluid parameter (β) buoyancy parameter (N), mixed convection parameter (λ), Magnetic parameter (M) and Suction parameter (S). Observed temperature profile for Magnetic parameter (M), mixed convection parameter (λ), Thermophoresis parameter (Nt), Biot number (Bi), Heat source/sink Parameter (Hg), Thermal relaxation parameter (δT), Prandtl Number (Pr), Eckert number (Ec), Radiation parameter (R). Examined concentration profile for Activation Energy (A.E.), temperature difference (δ), Thermophoresis parameter (Nt), Magnetic parameter (M), chemical reaction rate constant (σ∗), parameter of Brownian motion (Nb), Solute relaxation parameter (δC), and Schmidt Number (Sc). Additionally, for a range of values, the local Sherwood number, skin friction coefficient, and local Nusselt number were obtained.